Analysis of the characteristics and management of perforated peptic ulcer from 2011 to 2022: A multicenter and retrospective descriptive study - Hiromasa Hoshi; Akira Endo; Koji Ito; Tomohiro Akutsu; Hikaru Odera; Hideto Shiraki; Kei Ito; Takeshi Yokoyama; Yasukazu Narita; Taro Masuda; Akira Suekane; Koji Morishita (Annals of Gastroenterological Surgery)
Abstract Aim Although perforated peptic ulcer is common in Japan, few large‐scale studies have assessed its management, including surgical procedures and outcomes. This study aimed to survey the characteristics, management, and outcomes of perforated peptic ulcer. Methods A multicenter retrospective descriptive analysis was conducted across seven centers in Japan between 2011 and 2022. Perforated peptic ulcer was defined as gastric or duodenal ulcer perforation, excluding malignant or iatrogenic perforation. Results We enrolled 703 patients with perforated peptic ulcer. The overall in‐hospital mortality rate was 35/703 (5.0%). Conservative treatment was performed as an initial treatment in 217/703 (30.9%) patients, among whom 52 (24.0%) eventually underwent surgery. The median age (interquartile range) of patients who successfully completed the conservative treatment was 60 (46–71) years. A total of 538/703 (76.5%) patients underwent surgery. The gastrectomy percentage increased with the perforation diameter. The anastomotic leakage rate for gastrectomy was high in 10/66 (15.2%) patients. Laparoscopy was performed in 115/538 (21.4%) patients, among whom 23 (20.0%) were converted to open surgery. Patients who underwent laparoscopy had a perforation diameter ≤ 20 mm. The use of laparoscopy varied among facilities, ranging from 1.8% to 61.2%. Conclusion The in‐hospital mortality rate for perforated peptic ulcer in this study was 5.0%, and conservative treatment was safely performed even in elderly patients. As the perforation diameter increased, the rate of gastrectomy tended to rise, and the rate of anastomotic leakage in those patients was high. UMIN Clinical Trials Registry; UMIN000054391.